EFFECTIVE UTILIZATION OF INFORMATION SYSTEMS IN A GAS-TRANSPORT INFRASTRUCTURE OF REPUBLIC UZBEKISTAN - Omonilla S. Umarov (Статистика и экономика)
Present article is devoted questions of optimization of maintenance by natural gas of industrial production in Republic Uzbekistan, to a place and a role of the information systems in maintenance with natural gas of the population of the country and efficiency of functioning of gas-transport branch in the country as a whole.